A comparative study of three different root canal curvature measurement techniques and measuring the canal access angle in curved canals - (:unkn) unknown (ELSEVIER SCIENCE INC, 2005)
In the first part of this study the Schneider (S), Weine (W), and Long-Axis (LA) techniques are used for comparing the measurement of canal curvature. One hundred mandibular first and second molar teeth were selected. Radiographs were taken after inserting size 10 K-files into the mesiobuccal root canals. The radiographic findings were digitized on a computer, and the three different curvature angles were measured from drawings of the same root canal and compared statistically. ANOVA showed that there were significant differences between the curvature angle values determined using each technique (p < 0.001). In the second part of this study the term canal access angle (CAA) was introduced and it was defined by examining the morphology of canal curvature. Canal length, curvature distance (y), curvature height (x), Schneider angle, and the newly defined CAA were evaluated statistically. Using a multiple regression analysis, the CAA was significantly related to x (p < 0.001) and y (p < 0.005). There was a positive correlation (r = 0.74) between the CAA and curvature height (x). The results indicated that the CAA is a more effective way of evaluating the root canal curvature.
Keywords: ROTARY NICKEL-TITANIUM; BALANCED FORCE TECHNIQUE; ENDODONTIC INSTRUMENTS; CYCLIC FATIGUE; BREAKAGE; SYSTEMS; MOLARS; TORQUE; FILES